RECYCLING OF WASTES OF PETROLEUM REFINING INDUSTRY BY USING THEM IN THE MANUFACTURE OF TIRE RUBBERS - Turebekova G.Z.; Shapalov Shermakhan Kuttibayevich; Issayev Gany Isaulu; Alpamysovа Gulzhayna Baigonysova; Bitimirovа Aliya; Lyubchyk Svitlana; Yergubekova Zhanat Saparbekovna; Pusurmanova Gulzhamal Zhusupbekovna (Academic Scientific Journal of Chemistry, 2019)
The important scientific direction of petrochemistry is manufacture of plasticizers, softeners, vulcanizing agents, fillers on the basis of industrial wastes.This allows expand the raw-material base, use heavy stocks of refinery wastes, reduce technogenic influence on the environmentand solve the problem of manufacture of import-substituting softeners for the rubber-processing industry of Kazakhstan. The feature of Kazakhstan petroleum is high concentration of sulfur compounds, in consequence of which much sulfuric wastes are formed, which are environmentally hazardous in open storage. Optimization of a receipt for developed rubber compounds for manufacture of a filler strip for passenger car tire beads was carried out in our work by serial analysis of influence of content of each of the components separately (sulfur and oil sludge) at the fixed amount of other ingredients on the rubber properties. In order to identify optimal amount of organic share of the oil sludge in the content of rubber compounds, rubber compounds with different content of organic share of the oil sludge were gained. Plasticizers and softeners were substituted to the organic share of the oil sludge. Also polymeric and colloidal sulfur mixture of Tengiz field was used as a vulcanizing agent in the receipts of rubber compounds. The results of comprehensive tests showed replaceability of traditionally used in the rubber compounds softeners to the organic share of the oil sludge and use of Tengiz sulfur as a vulcanizing agent.